Formulation, Characterization, in vitro and MTT Cytotoxicity Evaluation of Pioglitazone HCl Films for Topical Administration - Singh, Karishma; Mehrotra, Archana; Singh, Sobhna (Indian Journal of Pharmaceutical Education and Research)
Aim: The main focus of the study was to create and analyze novel formulation to explore the potential of Pioglitazone HCl with Guar Gum, Chitosan and Sodium alginate for topical delivery and evaluate them. Materials and Methods: Pioglitazone HCl loaded films were formulated by solvent evaporation technique and were subsequently incorporated within the Guar gum and Chitosan. Results: For the investigation, various physicochemical parameters along with in vitro drug release studies, and accelerated stability study were performed. MTT assay with the drug-loaded films were also conducted. The thickness and weight uniformity were excellent in Chitosan and Gaur Gum films. The percentage moisture loss and absorption tests indicated that the films maintained balanced moisture content. The surface pH of the films was found to be within a range that is generally compatible with skin application, minimizing the risk of irritation. The in vitro drug release and kinetic investigations revealed that all batches exhibited a controlled and sustained release of Pioglitazone HCl over an 8-hr period. The release kinetics have been explored by using four different models: Zero-Order, First-Order, Higuchi, and Korsmeyer-Peppas. The Korsmeyer-Peppas models excellent fit across all batches. MTT assay shows that all formulations (F1 to F6) exhibited a similar trend of moderate cytotoxicity at higher concentrations, with % viability decreasing as the concentration increased. F3, F4, F5, and F6 demonstrated slightly higher cytotoxicity than F1 and F2, as reflected in their lower IC50 values. The accelerated stability investigation showed that drug-loaded polymeric films were stable for up to two weeks under accelerated situations.
Keywords: In vitro Studies; MTT Assay Higuchi kinetics and Korsmeyer-Peppas Analysis; IC50 value.